PERGESERAN DARI SISTEM AKUNTANSI KONTINENTAL KE SISTEM AKUNTANSI ANGLO-SAXON DI INDONESIA - Nugroho, Mahendra Adhi; Aulia, Nida; Lestari, Hanifah; Novitasari, Budi Tiara (Yudishtira Journal : Indonesian Journal of Finance and Strategy Inside, 2023)
The development of the accounting system in Indonesia began with the continental accounting system during the Dutch period, then changed to the Anglo-Saxon accounting system due to the large number of international transactions. The research method in this article is through a qualitative approach where the data collection technique is carried out by library research and the data analysis method used in this study is descriptive analysis. The data source used is secondary data. This study explains the changes and the advantages and disadvantages of both accounting systems. The final section of this study discusses how technology can affect the transition of the continental accounting system to the Anglo-Saxon accounting system. This study is expected to provide another perspective on how accounting system practices can change according to their environment